2008
DOI: 10.2353/ajpath.2008.080042
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Atheroma-Enriched Protein, SPRR3, in Vascular Smooth Muscle Cells through Cyclic Strain is Dependent on Integrin α1β1/Collagen Interaction

Abstract: Atherosclerotic plaques express high levels of small proline-rich repeat protein (SPRR3), a previously characterized component of the cornified cell envelope of stratified epithelia, where it is believed to play a role in cellular adaptation to biomechanical stress. We investigated the physiological signals and underlying mechanism(s) that regulate atheroma-enriched SPRR3 expression in vascular smooth muscle cells (VSMCs). We showed that SPRR3 is expressed by VSMCs in both human and mouse atheromas. In culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 70 publications
3
36
0
Order By: Relevance
“…Therefore, we investigated the expression of PTEN and phospho-PI3K in SPRR3-overexpressing cells, and found that these proteins were not significantly altered by SPRR3 expression (data not shown). It was recently reported that increased α1β1-integrin enhances SPRR3 expression (33), and integrin could induce AKT activation through the integrinassociated protein ILK (integrin-linked kinase) (34,35). The molecular mechanisms underlying the activation of AKT by SPRR3 are not clear, and further investigation is therefore needed to elucidate the specific mechanisms.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…Therefore, we investigated the expression of PTEN and phospho-PI3K in SPRR3-overexpressing cells, and found that these proteins were not significantly altered by SPRR3 expression (data not shown). It was recently reported that increased α1β1-integrin enhances SPRR3 expression (33), and integrin could induce AKT activation through the integrinassociated protein ILK (integrin-linked kinase) (34,35). The molecular mechanisms underlying the activation of AKT by SPRR3 are not clear, and further investigation is therefore needed to elucidate the specific mechanisms.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…For example, expression of ␣ 1 ␤ 1 integrin within VSMCs of an atheroma alters signal transduction downstream of cyclic strain and possibly other biomechanical forces as well matrix/cell interactions differentially within the cells comprising the atheroma resulting in unique gene expression. 31 This demonstrates the need to recapitulate multiple features of the in vivo microenvironment when studying vascular biology in vitro. Not only should the cellular and ECM components be consistent with the physiological context, but the mechanical strains of the system should also be accounted for when working in vitro.…”
Section: Cellular Changes Resulting From Biomechanical Stressmentioning
confidence: 99%
“…[31][32][33] However, within the context of vascular pathologies such as hypertension and atherosclerosis, certain mechanosensors are differentially regulated. For example, the angiotensin type I receptor, which has been shown to be a mechanosensor in VSMCs, is up-regulated in atherosclerosis.…”
Section: Cellular Changes Resulting From Biomechanical Stressmentioning
confidence: 99%
See 2 more Smart Citations